Real-world analysis of the efficacy and safety of lorlatinib in ALK-positive non-small cell lung cancer patients in China - Tian, Guangming; Nie, Jun; Dai, Ling; Hu, Weiheng; Zhang, Jie; Wu, Di; Ma, Xiangjuan; Chen, Xiaoling; Han, Sen; Han, Jindi; Zhang, Ziran; Long, Jieran; et al. (Frontiers in Oncology, 2025)
IntroductionLorlatinib, a third-generation ALK inhibitor, has demonstrated strong efficacy in treating advanced ALK-positive NSCLC, though real-world data, particularly from China, are limited. This study evaluates the real-world efficacy and safety of lorlatinib in Chinese patients with advanced ALK-positive NSCLC.Materials and methodsThis retrospective study analyzed 65 patients with advanced ALK-positive NSCLC who received lorlatinib at Peking University Cancer Hospital between September 2017 and August 2024. The study assessed the overall response rate (ORR), progression-free survival (PFS), and safety outcomes, comparing first-line treatment to subsequent treatments after prior ALK inhibitor exposure.ResultsThe real-world ORR (rwORR) for all patients was 49.2%, with a real-world disease control rate (rwDCR) of 92.3%. In the first-line treatment group (n=8), lorlatinib showed an ORR of 100%, and no patients experienced progressive disease (PD) during a median follow-up of 9 months. The mPFS for the entire cohort was 37.83 months, with the median OS (mOS) not reached (NR, 95% CI: NR-NR). Patients who had received one prior ALK inhibitor had a mPFS of 49.73 months, while those who had received two or more prior ALK inhibitors had a mPFS of 12.17 months. A statistically significant difference in mOS was found between patients with one prior ALKi and those with two or more prior ALKis (p = 0.032). Lorlatinib demonstrated strong intracranial efficacy, with a 45.2% intracranial ORR in patients with brain metastases. The safety profile was consistent with previous reports, with the most common AEs being hyperlipidemia. However, the incidence of severe AEs was manageable with dose adjustments and supportive treatments.ConclusionsLorlatinib demonstrates strong efficacy and manageable safety, especially in first-line treatment of advanced ALK-positive NSCLC, supporting its role as an effective treatment option.